1994
DOI: 10.1007/bf01083222
|View full text |Cite
|
Sign up to set email alerts
|

A structural synthesis of the Proterozoic Arabian-Nubian Shield in Egypt

Abstract: Detailed structural geological and related studies were carried out in a number of critical areas in the Proterozoic basement of eastern Egypt to resolve the structural pattern at a regional scale and to assess the general characteristics of tectonic evolution, orogeny and terrane boundaries. Following a brief account of the tectonostratigraphy and timing of the orogenic evolution, the major structural characteristics of the critical areas are presented. Collisional deformation of the terranes ended about 6 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
133
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(142 citation statements)
references
References 25 publications
9
133
0
Order By: Relevance
“…Meatiq-, Hafafit-, and Sibai Gneiss Domes; Fig. 1) (Sturchio et al 1983;Fowler and Osman 2001;Greiling et al 1994). The appearance and formation of the gneiss domes are interpreted to be closely linked to tectonic activity along the northward continuation of the Najd Faults System (e.g.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Meatiq-, Hafafit-, and Sibai Gneiss Domes; Fig. 1) (Sturchio et al 1983;Fowler and Osman 2001;Greiling et al 1994). The appearance and formation of the gneiss domes are interpreted to be closely linked to tectonic activity along the northward continuation of the Najd Faults System (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…2 (frame) ortho-and paragneisses, formed as a result of NW translation of the eugeoclinal thrust sheet during the East African orogeny (e.g. Greiling et al 1994). Loizenbauer et al (2001) interpreted the Meatiq Gneiss Dome to be a metamorphic core complex formed by orogen-parallel crustal extension following thrusting.…”
Section: Regional Geologymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the timing of deformation we note the important difference between the northernmost ANS and more southern ANS segments. In the Central Eastern Desert of Egypt as well as in NW Arabia deformation younger than 620 Ma generally associated with the Najd Fault System is common (Greiling et al 1994).…”
Section: Geology Of the Study Areamentioning
confidence: 99%
“…The region is composed of metapelitic schists, gneisses and granites and is cut by a number of dykes of different compositions, together with various types of aplitic and pegmatitic veins. Greiling et al (1994) concluded that post collisional evolution in Eastern Desert of Egypt started with extensional collapse, which was followed by NNW-SSE shortening and related large -scale thrusting (toward the NNW) and folding, distributed all over the Eastern Desert, followed by further period of Late to Postactivity. Assaf et al (2000) studied the polyphase folding in Nugrus-Sikait area and reported that the lithological constitution of the area comprise a sequence of dismembered ophiolites, ophiolitic mĂ©lange association and arc assemblage.…”
Section: Introductionmentioning
confidence: 99%